Legality of Halal Food Certification on Maslahah Mursalah Perspective - Wahyu Abdul Jafar (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study aims to comprehensively determine the legality of halal certification on food circulating in the community. Researchers reviewing the legality of halal food certification use the maslahah mursalah approach. Maslahah mursalah is more appropriate to use because the issue of halal food certification does not yet have a specific argument that discusses it. This study includes literature research with a normative approach. The data collection technique used in this research is the documentation technique. While the analysis technique used is the inductive analysis technique. The result of this study is that halal certification of eating based on maslahah mursalah follows Islamic law. There are many benefits of halal food certification following Islamic law principles. Food products that have obtained the halal certification label will give consumers a stronger sense of confidence that this food is genuinely halal ( al-halal bayyinun ) because a competent and authorized institution has verified it. It is different if a meal does not yet have a halal certification label, then consumers can doubt and be unsure about the halalness and quality of the product. The quality of food products that are doubtful of their halalness can change the law from halal to subhat; it is a different case if the product is already labeled with a halal certificate, consumers will be more sure of the quality and halalness of the product